The safety and efficacy of alfentanil combined with midazolam in fiberoptic bronchoscopy sedation: A randomized, double-blind, controlled trial - Wang, Longfei; Wu, Qiuyue; Wang, Ming; Ming, Wanquan; Sheng, Cheng; Zhang, Yonghua; Chen, Yongbin; Cao, Yunfei (Frontiers in Pharmacology, 2022)
Sedation is recommended by most guidelines to be offered to all patients undergoing diagnostic flexible bronchoscopy (DFB) without contraindications, and the most commonly reported regimen is midazolam in combination with a short-acting opioid (fentanyl or alfentanil) to provide both sedative and antitussive effects. However, the optimal dose or ideal regimen of the combination therapy with midazolam and opioids has not yet been found. So this randomized, double-blinded clinical trial was designed and registered (ChiCTR2100049052) to assess the safety and efficacy of midazolam combined with different doses of alfentanil in DFB sedation. Our study showed that relative high doses of alfentanil (10–25 μg/kg) combined with a fixed low dose of midazolam can markedly reduce hemodynamic fluctuations, cough reactions, patients’ discomforts, and improve their satisfaction in a dose-dependent manner during DFB, with no significant increase in the desaturation risks.